Ethnopharmacological study of traditional medicinal plants used by the people in Metema district, northwestern Ethiopia - Tadesse, Daniel; Lulekal, Ermias; Masresha, Getinet (Frontiers in Pharmacology, 2025)
BackgroundMedicinal plants are used by more than 80% of Ethiopians. The Metema District, shaped by various ethnicities and settlement histories, remains underexplored. This study aimed to document and analyze medicinal plant use and associated traditional knowledge in the local population.MethodsData were collected through semi-structured interviews, guided field walks, and focus-group discussions. A total of 110 informants participated in the study, using various sampling techniques. The informant consensus factor (ICF) and direct matrix ranking (DMR) were computed along with descriptive statistics to analyze the basic ethnobotanical data.ResultsIn this study, 85 therapeutic plants were utilized to treat 13 disease categories. The three ethnic groups shared 21.18% of their knowledge of medicinal plants. Fabaceae was the most represented family, comprising 11 plant taxa. Herbs were the predominant plant form (42.4%), leaves being the most frequently used (30.5%). Oral administration was the primary method used for the plant extracts (52.3%). Circulatory and blood-related disorders had the highest ICF value (0.91). Ziziphus spina-christi, Ximenia americana, and Ficus sycomorus were ranked as the top multipurpose plants. Fuelwood collection and agricultural expansion have been identified as the major threats to these plants.ConclusionThis study revealed the rich diversity of medicinal plants and traditional knowledge in the Metema District. The therapeutic potential of the documented plants supports further pharmacological investigations, underscoring the importance of preserving indigenous knowledge and protecting plant resources against ongoing threats.